2020
DOI: 10.1183/16000617.0028-2020
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic intratumoural therapies for non-small cell lung cancer

Abstract: The past decade has brought remarkable improvements in the treatment of non-small cell lung cancer (NSCLC) with novel therapies, such as immune checkpoint inhibitors, although response rates remain suboptimal. Direct intratumoural injection of therapeutic agents via bronchoscopic approaches poses the unique ability to directly target the tumour microenvironment and offers several theoretical advantages over systemic delivery including decreased toxicity. Increases in understanding of the tumour microenvironmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…A phase 2 trial was presented at ESMO 2021 which showed favorable survival data when used in combination with nivolumab in the second and third line treatment of advanced NSCLC ( 148 ). A plethora of approaches are currently underway which utilize intratumoral administration of various forms of immunotherapy, including gene therapies, cellular therapies, and immunostimulatory compounds are currently being evaluated ( 149 ).…”
Section: The Current Immunotherapy Landscape For the Treatment Of Nsclcmentioning
confidence: 99%
“…A phase 2 trial was presented at ESMO 2021 which showed favorable survival data when used in combination with nivolumab in the second and third line treatment of advanced NSCLC ( 148 ). A plethora of approaches are currently underway which utilize intratumoral administration of various forms of immunotherapy, including gene therapies, cellular therapies, and immunostimulatory compounds are currently being evaluated ( 149 ).…”
Section: The Current Immunotherapy Landscape For the Treatment Of Nsclcmentioning
confidence: 99%
“…91 92 93 The central goal of research thus far has been to evaluate the safety and feasibility of these therapies, with the majority of side effects reported being related to the administration technique (commonly endobronchial ultrasound-guided transbronchial needle injection), or local irritation from extravasation of an antineoplastic agents into the airway or other adjacent structures. 91…”
Section: Bronchoscopic Interventions For Malignant Central Airway Obs...mentioning
confidence: 99%
“…[91][92][93] The central goal of research thus far has been to evaluate the safety and feasibility of these therapies, with the majority of side effects reported being related to the administration technique (commonly endobronchial ultrasound-guided transbronchial needle injection), or local irritation from extravasation of an antineoplastic agents into the airway or other adjacent structures. 91 There are a host of potential benefits related to bronchoscopic administration of antineoplastic agents, including the ability to reach a higher tissue concentration than with systemic administration, reduced toxicity, and potential synergy with other local therapies. 91 A multicenter, singlearm, open-label trial of 90 patients with NSCLC and MCAO published in 2016 represents the largest study to date.…”
Section: Intratumoral Antineoplastic Therapymentioning
confidence: 99%
“…Chemotherapy along with anti-angiogenic drugs or radiotherapy is also administered in the case where no gene expression is identified. Intratumoral treatment administration has been previously proposed and administered in advanced stage patients in order to shrink a large tumor that blocks an airway or where systemic therapy was not possible [13][14][15][16][17][18][19]. It has been previously investigated that the higher the expression of PD-L1 the more efficient is the immunotherapy [20].…”
Section: Introductionmentioning
confidence: 99%